An Advanced Model for Greenhouse Gas Emission Reduction in the Agricultural Sector to Achieve Sustainability for Thailand’s Future - Pruethsan Sutthichaimethee; Phayom Saraphirom; Chaiyan Junsiri (Applied Sciences, 2025)
This research aimed to develop an advanced model for sustainably reducing greenhouse gas emissions in the future. The research employs a quantitative research approach, introducing a new model called the Structural Equation Modeling with Vector Autoregressive Latent Trajectory Model (SEM-VALTM). This model differs significantly from previous models as it identifies strategic pathways for effective national administration, ensuring high performance without spurious results, surpassing the efficiency of earlier models. The findings reveal that the environmental sector is directly affected by the economic sector, with the relationship exhibiting an inverse direction. Similarly, the environmental sector is influenced by the social sector, also in an opposing direction. The SEM-VALTM model contributes new knowledge, highlighting that the environmental sector demonstrates the slowest adjustment toward equilibrium (6%). Under a sustainability policy framework, it was found that the economic sector, particularly the industrial rate, has the highest influence on economic changes, which in turn have the most significant negative impact on the environment. The study further projects that from 2025 to 2037, greenhouse gas emissions will rise sharply, reaching 95.05 Mt CO2 Eq., exceeding the carrying capacity threshold of 60.5 Mt CO2 Eq. Based on risk management principles, continuous measures must be implemented to reduce greenhouse gas emissions. Therefore, the government must establish a new scenario policy emphasizing renewable energy and clean technologies as substitutes. The findings suggest that future energy consumption will consistently decrease, resulting in greenhouse gas emissions of 50.04 Mt CO2 Eq. (2025–2037), which is below the carrying capacity.